PERBEDAAN MEDIA POSTER DAN KARIKATUR TERHADAP KETERAMPILAN MENULIS PADA SISWA KELAS III DI MIS DAARUL MUQIMIEN - Erdhita Oktrifianty; Rolisti Amelia (Universitas Muhammadiyah Tangerang, 2021)
third graders in MIS Daarul Muqimien. The samples of this study were 15 students in class III-A (Experimental Class I taught with poster learning media) and 15 students in class III-B (Experimental Class II taught with caricature learning media). Data analysis was performed by t-test. These findings indicate that: (1) The learning outcomes of students taught with caricature learning media are better with an average score of 78.73 than students' learning outcomes taught by caricature learning media with an average value of 73.73 (2) There are differences which is significant in student learning outcomes taught with posters and caricature learning media on writing skills in descriptive essay writing material in class III MIS Daarul Muqimien for the 2020/2021 school year. This is in accordance with the t-test calculation, that based on the calculation results obtained tcount = 6.970 this result is compared with ttable at the real level = 0.05 and dk = 28, namely ttable = 1.70 then tcount > ttable = 6.970 > 1.70. The conclusion of this study explains that there is a significant difference in student learning outcomes taught by poster and caricature learning media on writing skills in descriptive essay writing material in class III MIS Daarul Muqimien in the 2020/2021 school year.